2009
DOI: 10.1111/j.1574-695x.2008.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofHelicobacter pyloripathogenicity-associatedcagAandvacAgenotypes among Pakistani dyspeptic patients

Abstract: The cytotoxin-associated gene A (cagA), and the vacuolating cytotoxin gene A (vacA) products are considered the most important pathogenic determinants of Helicobacter pylori, a gram-negative bacterium causing gastrointestinal disorders such as duodenal ulcers, gastritis and mucosa-associated lymphoid tissue disease. A higher prevalence of H. pylori has been reported in various regions in the Pakistani population; however, no data are available about the virulence-associated genetic determinants. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 25 publications
5
35
6
Order By: Relevance
“…Our report and another from Yakoob et al confirm the decreasing trend of H. pylori infection overtime in Karachi, which is comparable to trends seen in other South Asian and European countries [44][45][46]. Interestingly, earlier studies from northern and central parts of Pakistan reported 66% and 84% prevalence rates among dyspeptic patients [25,29], indicating the difference in H. pylori infection in geographic niches and ethnic groups in Pakistan. Interestingly cagA gene analysis further confirms the above-mentioned observation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our report and another from Yakoob et al confirm the decreasing trend of H. pylori infection overtime in Karachi, which is comparable to trends seen in other South Asian and European countries [44][45][46]. Interestingly, earlier studies from northern and central parts of Pakistan reported 66% and 84% prevalence rates among dyspeptic patients [25,29], indicating the difference in H. pylori infection in geographic niches and ethnic groups in Pakistan. Interestingly cagA gene analysis further confirms the above-mentioned observation.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies reported the high rate of H. pylori infection in the country based on serological, bacteriological, and histological observations [25][26][27]. Recent reports, however, document the prevalence of the vacA s1m1 genotype in Pakistan, endorsing the common trend of other South Asian neighbors [28,29]. The presence of the organism in drinking water has also been reported, indicating greater chances of infection for the community [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…22 The distribution of vacAs1a and vacAs1b varies also between different areas in the same country, as in Pakistan and Chilli. 23,24 Contradictory to studies demonstrating a higher risk for development of peptic ulcer disease upon gastric infection with H. pylori strains containing type vacAs1 allele/subtypes 25 , we found that this correlation is non-significant, as shown in table 3. A similar finding has also been concluded from eastern Asia 26 , Iraq and Iran.…”
mentioning
confidence: 66%
“…Increased rates of H. pylori infection in developing nations such as Pakistan, Vietnam, Bangladesh and India, which combat poverty, poor sanitary conditions and overcrowding, indicate the role of environmental factors in the transmission of infection [17][18][19][20]. In 2007, Ahmed et al indicated that the risk of H. pylori infection can be reduced by improving personal hygiene and regular use of boiled drinking water [20].…”
Section: Resultsmentioning
confidence: 99%